A space of transition and transaction: A rejoinder to selected commentaries on place spirituality. (March 2019) - Counted, Victor; Watts, Fraser
This rejoinder acknowledges the empirical gaps and theoretical/theological disharmony highlighted in the three selected commentaries on Place Spirituality (PS), but we defend our central argument about the developmental pathways of PS. First, we provide an overview of recent studies on PS, highlighting what has been done so far in the field. Second, we draw from the commentaries to advance the understanding of PS in relation to three world religions: Islam, Christianity and Hinduism. Third, we evaluate the normative aspects of PS as a transactional versus transitional phenomenon. Finally, we defend the two contested developmental pathways to PS, involving the compensation and correspondence working models of attachment, while complementing these models using the motivational systems framework. We maintain that these models are relevant for understanding the relationship between religious attachment and place attachment among religious and non-religious people. Recommendations for further studies are made in relation to the broader implications of PS.